The Role of Physical and Non-Physical Programs in Enhancing Community Well-being Through the Leadership Style of Village Government - Andi Nadirah M. (Kontigensi : Jurnal Ilmiah Manajemen, 2023)
Community welfare is a key indicator of a nation's progress. To achieve sustainable welfare, a holistic approach involving various factors is necessary, including physical and non-physical programs implemented through effective leadership styles, encompassing sports, training, education, and skills development. This research aims to identify the influence of physical and non-physical programs on community welfare through the leadership style of village government in Pongo Village, Masamba District, North Luwu Regency. The research method used is explanatory research with data collection through questionnaires, which were validated and tested for reliability before distribution. The population and sample of this study are the residents of Pongo Village selected through purposive sampling, with 102 respondents chosen according to the Moe formula for sampling determination. The collected data are analyzed using the SmartPLS statistical tool. The results indicate a significant impact of physical and non-physical programs on leadership style and community welfare. Additionally, leadership style has a significant influence on community welfare. Both physical and non-physical programs also directly contribute significantly to community welfare. The research further reveals an indirect influence, where physical programs significantly affect community welfare through leadership style.